Worm Pick Media Increases Early Childhood Numeracy Achievement: Worm Pick Media Meningkatkan Prestasi Numerasi Anak Usia Dini - Putri Rizky Nur Fadhilah; Luluk Iffatur Rocmah (Academia Open, 2025)
General Background: Early childhood education represents a critical developmental phase in which cognitive abilities, including numeracy skills, require appropriate stimulation during the golden age period. Specific Background: Children aged 4–5 years at Mutiara Anak Sholeh Sukodono Kindergarten demonstrated low counting ability, indicating the need for appropriate instructional media to support learning activities. Knowledge Gap: Limited classroom-based evidence exists regarding the use of interactive manipulative learning media to support counting skill development among preschool children. Aims: This study aims to examine the use of Worm Pick learning media to support numeracy development among children aged 4–5 years. Results: This study applied Classroom Action Research using observation and interview techniques. Initial observation indicated that children’s counting ability was categorized as low with a percentage of 6.25% in the pre-cycle. Implementation of Worm Pick learning media increased children’s numeracy performance to 31.25% in cycle I and 87.5% in cycle II, demonstrating progressive improvement across learning stages. Novelty: The study introduces the application of Worm Pick as a hands-on instructional medium integrated into structured classroom action cycles for preschool numeracy development. Implications: The findings provide practical guidance for early childhood educators in utilizing interactive manipulative media to support cognitive learning processes and strengthen numeracy instruction strategies in kindergarten settings.  Highlights: Interactive Counting Tool Demonstrated Progressive Percentage Growth Across Learning Cycles. Baseline Assessment Indicated Very Low Mathematical Readiness Among Participants. Structured Intervention Stages Supported Measurable Developmental Progression. Keywords: Worm Pick Learning Media, Preschool Numeracy, Classroom Action Research, Manipulative Learning Tools, Kindergarten Cognitive Development